2008
DOI: 10.2337/db08-0688
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy With Glucagon-Like Peptide-1 and Gastrin Restores Normoglycemia in Diabetic NOD Mice

Abstract: OBJECTIVE-Glucagon-like peptide-1 (GLP-1) and gastrin promote pancreatic ␤-cell function, survival, and growth. Here, we investigated whether GLP-1 and gastrin can restore the ␤-cell mass and reverse hyperglycemia in NOD mice with autoimmune diabetes.RESEARCH DESIGN AND METHODS-Acutely diabetic NOD mice were treated with GLP-1 and gastrin, separately or together, twice daily for 3 weeks. Blood glucose was measured weekly and for a further 5 weeks after treatments, after which pancreatic insulin content and ␤-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
113
3
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(124 citation statements)
references
References 41 publications
6
113
3
2
Order By: Relevance
“…Zhang et al 5 have demonstrated that continuous infusion of GLP-1 in pre-diabetic NOD mice results in significant delay in the onset of diabetes as a result of increased beta-cell proliferation coupled with decrease in beta-cell apoptosis. Furthermore, combination therapies using GLP-1 or exendin-4 with gastrin, 48 anti-lymphocyte serum 49 or anti-CD3 immunotherapy 50 have been shown to restore normoglycemia in acutely diabetic NOD mice by increasing insulin stores and reducing beta-cell apoptosis. Thus, GLP-1-receptor agonists may be useful in therapeutic management of individuals with either type-1 or type-2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al 5 have demonstrated that continuous infusion of GLP-1 in pre-diabetic NOD mice results in significant delay in the onset of diabetes as a result of increased beta-cell proliferation coupled with decrease in beta-cell apoptosis. Furthermore, combination therapies using GLP-1 or exendin-4 with gastrin, 48 anti-lymphocyte serum 49 or anti-CD3 immunotherapy 50 have been shown to restore normoglycemia in acutely diabetic NOD mice by increasing insulin stores and reducing beta-cell apoptosis. Thus, GLP-1-receptor agonists may be useful in therapeutic management of individuals with either type-1 or type-2 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The ␣-cells synthesized glucagon-like peptide-1 (GLP-1), a potent growth factor for ␤-cells and their precursors (40,46), in addition to glucagon. ␣-Cell aggregates devoid of ␤-cells, which decline in abundance with age, have been observed in the head of the neonatal rat pancreas (1).…”
Section: Discussionmentioning
confidence: 99%
“…Advances in our understanding of cell signaling pathways and mechanistic studies of existing drugs have identified synergistic therapeutic targets that may be concurrently utilized for more effective cancer treatments (3). Combination drug therapy is an attractive strategy, one that is used routinely to treat diseases like malaria (4), HIV/AIDS (5), diabetes (6), and cancer (3). Unlike single-agent chemotherapy, combination chemotherapy offers advantages such as signaling different pathways in cancer cells, maximizing therapeutic efficacy against individual targets, and overcoming mechanisms of resistance.…”
mentioning
confidence: 99%